2012
DOI: 10.1200/jco.2012.30.15_suppl.505
|View full text |Cite
|
Sign up to set email alerts
|

13-gene signature to predict rapid development of brain metastases in patients with HER2-positive advanced breast cancer.

Abstract: 505 Background: Brain metastases (BM) of breast cancer constitute an important part of therapeutic failures and are associated with severe morbidity and mortality. The risk of BM is particularly high in HER2+ advanced breast cancer pts. We earlier developed in this group a 13-gene signature strongly predicting for rapid development of BM (J Clin Oncol 2008; 26: 45s). Now, we validated these results in an independent group of pts and on culture model system. Methods: Discovery group included 87 samples analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In order to increase the potential clinical applicability of this signature, a qRT-PCR based analysis of the 13 genes (and 3 references) was performed and showed promising preliminary results [ 15 , 16 ]. The TaqMan gene expression assay IDs for each gene was chosen to meet FFPE sample requirements for custom TLDA based on Applied Biosystems guidelines.…”
Section: Resultsmentioning
confidence: 99%
“…In order to increase the potential clinical applicability of this signature, a qRT-PCR based analysis of the 13 genes (and 3 references) was performed and showed promising preliminary results [ 15 , 16 ]. The TaqMan gene expression assay IDs for each gene was chosen to meet FFPE sample requirements for custom TLDA based on Applied Biosystems guidelines.…”
Section: Resultsmentioning
confidence: 99%
“…These studies often share a common goal of being able to predict the risk of BrM at the point of primary cancer diagnosis. For example, Duchnowska identified a 13 gene BrM prediction signature for HER2+ breast cancer [ 28 ], and this was further refined to a 3 gene classifier that included RAD51 (RAD51 homolog), HDGF (hepatoma-derived growth factor), and TPR (translocated promoter region) genes. Interestingly, multivariate analysis revealed that this 3 gene signature was highly predictive of early BrM in the discovery cohort, but it was not confirmed in the validation cohort.…”
Section: Biomarkers For Prognostication and Differential Diagnosis Of...mentioning
confidence: 99%
“…A better understanding of the molecular background of the mechanisms of brain metastasis could help in the development of new treatment strategies or treatment algorithms. One study has in fact reported that genes from the HER2 signal transduction pathway and DNA repair genes can help [21]. The time interval until onset of brain metastasis was 54 months in a group identified with a high-risk gene signature vs. 86 months in the low-risk group (p = 0.038).…”
Section: Lapatinib In the Neoadjuvant Therapy Settingmentioning
confidence: 99%